Plastid Located WHIRLY1 Enhances the Responsiveness of Arabidopsis Seedlings Toward Abscisic Acid - Isemer, Rena; Krause, Kirsten; Grabe, Nils; Kitahata, Nobutaka; Asami, Tadao; Krupinska, Karin (Frontiers in Plant Science, 2012)
WHIRLY1 is a protein that can be translocated from the plastids to the nucleus, making it an ideal candidate for communicating information between these two compartments. Mutants of Arabidopsis thaliana lacking WHIRLY1 (why1) were shown to have a reduced sensitivity towards salicylic acid (SA) and abscisic acid (ABA) during germination. Germination assays in the presence of abamine, an inhibitor of ABA biosynthesis, revealed that the effect of SA on germination was in fact caused by a concomitant stimulation of ABA biosynthesis. In order to distinguish whether the plastid or the nuclear isoform of WHIRLY1 is adjusting the responsiveness towards ABA, sequences encoding either the complete WHIRLY1 protein or a truncated form lacking the plastid targeting peptide were overexpressed in the why1 mutant background. In plants overex¬pressing the full-length sequence, WHIRLY1 accumulated in both plastids and the nucleus, whereas in plants overexpressing the truncated sequence, WHIRLY1 accumulated exclusively in the nucleus. Seedlings containing recombinant WHIRLY1 in both compartments were hypersen¬sitive towards ABA. In contrast, seedlings possessing only the nuclear form of WHIRLY1 were as insensitive towards ABA as the why1 mutants. ABA was furthermore shown to lower the rate of germination of wildtype seeds even in the presence of abamine which is known to inhibit the formation of xanthoxin, the plastid located precursor of ABA. From this we conclude that plastid located WHIRLY1 enhances the responsiveness of seeds towards ABA even when ABA is supplied exogenously.